A BIBLIOMETRIC ANALYSIS OF ARTICLES PUBLISHED IN THE JOURNAL OF ACCOUNTING AND AUDITING DURİNG 2017 - 2023 - Kaya, Gamze Ayça (TÜRMOB, 2024)
It is aimed to examine the bibliometric characteristics of the articles published in the Journal of Accounting and Auditing during 2017 – 2023. A total of 246 articles in 20 issues of the journal are examined. Bibliometric analysis is used in the research. As a result of the research, it is determined that male authors are more than female authors and the majority of the articles are research articles in all other years except 2018. In addition, it is determined that the most articles are written by faculty members with the title of Assistant Professor the articles are mostly written with 2 authors and the authors mostly worked at Ankara Hacı Bayram Veli, Başkent ve Anadolu Universities, respectively. It is found that the most articles in the journal are written on 34 accounting standards, 23 accounting professionals and 11 accounting education and independent audit subjects, respectively.

Muhasebe ve Denetime Bakış Dergisi’nde 2017 – 2023 yılları arasında yayımlanan makalelerin bibliyometrik özelliklerinin incelenmesi amaçlanmıştır. Dergideki 20 sayıda yer alan toplam 246 makale incelenmiştir. Araştırmada, bibliyometrik analiz kullanılmıştır. Araştırmanın sonucunda; 2018 yılı hariç diğer yılların tamamında erkek yazarların kadın yazarlardan daha fazla ve makalelerin çoğunluğunun araştırma makalesi olduğu belirlenmiştir. Ayrıca, en fazla makaleyi Dr. Öğr. Üyesi unvanlı öğretim üyelerinin yazdıkları, makalelerin en fazla 2 yazarlı olarak yazıldıkları ve yazarların en fazla sırasıyla Ankara Hacı Bayram Veli, Başkent ve Anadolu Üniversitelerinde çalıştıkları tespit edilmiştir. Dergideki makalelerin en fazla sırasıyla 34 adet muhasebe standartları, 23 adet muhasebe meslek mensupları ve 11 adet muhasebe eğitimi ve bağımsız denetim konularında yazıldıkları bulunmuştur.
MUHASEBE VE DENETİME BAKIŞ DERGİSİ’NDE 2017 – 2023 YILLARI ARASINDAKİ YAYIMLANAN MAKALELERİN BİBLİYOMETRİK ANALİZ İLE İNCELENMESİ
Keywords: Business Administration; İşletme